2020
DOI: 10.1186/s12877-020-01899-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy interventions for older people with vertigo, dizziness and balance disorders addressing mobility and participation: a systematic review

Abstract: Background Vertigo, dizziness and balance disorders (VDB) are among the most relevant contributors to the burden of disability among older adults living in the community and associated with immobility, limitations of activities of daily living and decreased participation. The aim of this study was to identify the quality of evidence of physical therapy interventions that address mobility and participation in older patients with VDB and to characterize the used primary and secondary outcomes. Methods A systema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
(64 reference statements)
0
21
0
1
Order By: Relevance
“…This condition is named presbyvestibulopathy, and recently, strict diagnostic criteria have been published [13] with the aim of ensuring a suitable categorization and homogenization of these patients. At this time, no pharmacological treatment for presbyvestibulopathy is indicated, and a strong body of evidence supports the usefulness of vestibular rehabilitation [14].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is named presbyvestibulopathy, and recently, strict diagnostic criteria have been published [13] with the aim of ensuring a suitable categorization and homogenization of these patients. At this time, no pharmacological treatment for presbyvestibulopathy is indicated, and a strong body of evidence supports the usefulness of vestibular rehabilitation [14].…”
Section: Introductionmentioning
confidence: 99%
“…A fall is an obvious and severe outcome of dizziness or loss of balance ( 16 ). The close dependence between musculoskeletal abilities and balance functions are essential in order to allow an active lifestyle with a preserved quality of life ( 16 18 ). As a consequence, balance deficits, dizziness, and pain often lead to a decrease in activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review revealed that for older people, active physical therapy using vestibular rehabilitation, regardless of any variations and in combination with repositioning manoeuvres was most effective [ 24 ]. The second review identified barriers to and facilitators of successful implementation of CPWs within the context, implementation and setting dimensions of Context and Implementation of Complex Interventions (CICI) framework dimensions [ 31 ], which need to be considered in the implementation of CPWs [ 26 ].…”
Section: Results Stepmentioning
confidence: 99%
“…The second review identified barriers to and facilitators of successful implementation of CPWs within the context, implementation and setting dimensions of Context and Implementation of Complex Interventions (CICI) framework dimensions [ 31 ], which need to be considered in the implementation of CPWs [ 26 ]. Detailed results of systematic reviews are published elsewhere [ 24 , 26 ].…”
Section: Results Stepmentioning
confidence: 99%
See 1 more Smart Citation